The morphology of the Late Pleistocene hominin remains from the site of La Cotte de St Brelade, Jersey (Channel Islands). Issue 152 (March 2021) - Compton, Tim; Skinner, Matthew M.; Humphrey, Louise; Pope, Matthew; Bates, Martin; Davies, Thomas W.; Parfitt, Simon A.; Plummer, William P.; Scott, Beccy; Shaw, Andrew; Stringer, Chris
Abstract: Thirteen permanent fully erupted teeth were excavated at the Paleolithic site of La Cotte de St Brelade in Jersey in 1910 and 1911. These were all found in the same location, on a ledge behind a hearth in a Mousterian occupation level. They were originally identified as being Neanderthal. A fragment of occipital bone was found in a separate locality in a later season. Recent dating of adjacent sediments gives a probable age of <48 ka. The purpose of this article is to provide an updated description of the morphology of this material and consider its likely taxonomic assignment from comparison with Neanderthal and Homo sapiens samples. One of the original teeth has been lost, and we identify one as nonhominin. At least two adult individuals are represented. Cervix shape and the absence of common Neanderthal traits in several teeth suggest affinities with H. sapiens in both individuals, while crown and root dimensions and root morphology of all the teeth are entirely consistent with a Neanderthal attribution, pointing toward a possible shared Neanderthal and H. sapiens ancestry (the likely date of this material corresponds with the time in which both Neanderthals and H. sapiens were present in Europe). The occipital fragment is stratigraphically more recent and does not exhibit any diagnostic Neanderthal features.